Analysis of requests for reservation of blood concentrates in patients referred to urgent surgeries in a teaching hospital - Garcia, Cintia de Lelis; Silveira, Michelle Petrolli; Jesus-Silva, Seleno Glauber de (HSJ, 2023)
Introduction: The rates of request and use of blood concentrates are still poorly reported in the literature. This study aimed to analyze the rates of requests for blood concentrates and their use in patients undergoing emergency surgery in a teaching hospital. Methods: A retrospective, quantitative and descriptive study was conducted in 359 medical records of patients in urgent surgery scheduled with a request for a reserve of blood concentrate. The ratios between crossmatched and transfused units (C/T), transfusion index (TI), and probability (TP) were calculated, and the times between request and delivery at the transfusion agency (TA) and patient admission to the surgical center (SC). Results: The mean age was 58.5 ± 22.2 years, with the majority being male (53.1%). There was an average of 27.5 monthly requests (min 12, max 44). Ninety-seven units of blood concentrates were transfused into 44 patients (C/T ratio 7.59; TI 0.27; TP 12.3%). Only seven patients had their requests made after admission to the OR. The median time between the request and arrival at the TA was 1h15min, while that between the request and the patient's arrival at the SC was 5h23min. There was greater transfusion in major surgery (major 37, 14.8% vs. medium 7, 6.5%; p = 0.027) and non-orthopedic surgery (orthopedic 9, 4.0% vs. non-orthopedic 35, 26.9%; p < 0.001). Conclusion: there was a significant discrepancy between the number of requests for blood reservation and its real use and an increased time between reservation requests and their arrival at the TA.